CHARACTERIZATION OF AN ENTOMOPHAGOUS MEDICINAL FUNGUS CORDYCEPS SINENSIS (BERK.) SACC. OF UTTARAKHAND, INDIA - RUPESH KUMAR ARORA,; NIMISHA SINGH,; R. P. SINGH, (The Bioscan, 2013)
Higher altitudes of District Pithoragarh, Uttarakhand were surveyed for collection and isolation of the caterpillar fungus, Cordyceps sinensis. Fruiting bodies of C. sinensis were 4 -7cm long over the caterpillar cadaver ranging 3-4cm in size, mostly erect, stalked, slightly swollen at tip; emerged single, double or triple from the head of larvae. Of the five semi-synthetic media used, SDAY followed by PDA supported maximum growth of the fungus. Hyphae septate branched and 1-30μm wide; colony white to creamish or yellowish with lined depressions, later pink or orange, from reverse purple to purplish brown. Perithecia oval or egg shaped filled with a number of elongated, unitunicate, capitate, cylindrical and hyaline ascus. Optimum temperature and pH for mycelial growth was found to be 15ºC and 6.0.On the basis of these characteristics the fungus was identified as Cordyceps sinensis (Berk.) Sacc.